2019
DOI: 10.2147/cmar.s198411
|View full text |Cite
|
Sign up to set email alerts
|

<p>kshv-mir-k12-1-5p promotes cell growth and metastasis by targeting SOCS6 in Kaposi’s sarcoma cells</p>

Abstract: Background: Kaposi’s sarcoma (KS) is a highly disseminated angiogenic tumour of endothelial cells. Many deregulated miRNAs, including kshv-mir-k12-1-5p, have been identified in KS. kshv-mir-k12-1-5p plays important roles in KS. However, the underlying mechanism is not fully understood. The aim of this study was to investigate the exact functions of kshv-mir-k12-1-5p in KS cells. Materials and methods: The biological functions of kshv-mir-k12-1-5p were studied using CCK-8, apo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…For example, kshv-miR-K12-1, -3, and -4-3p target and inactivate the inducer of apoptosis, Casp3, blocking apoptosis [64], while kshv-K12-1 functions as an oncogene by activating NF-κB/IL-6/STAT3 signaling [65]. Kshv-mir-K12-3 has been demonstrated to be a promoter of cell migration and invasion by targeting GRK2/CXCR2/AKT signaling [66], and kshv-miR-k12-1-5p has been shown to be a promoter of the proliferation, migration, and invasion of KS cells by suppressing cytokine signaling 6 (SOCS6) [67]. It has also been demonstrated that kshv-miR-K1-5p and kshv-miR-K4-5p directly target CASTOR1, inhibiting its expression and activating the mTORC1 pathway with the final result of promoting tumorigenesis [68].…”
Section: Kaposi's Sarcoma Herpesvirus/human Herpesvirus-8 (Kshv/hhv8)mentioning
confidence: 99%
“…For example, kshv-miR-K12-1, -3, and -4-3p target and inactivate the inducer of apoptosis, Casp3, blocking apoptosis [64], while kshv-K12-1 functions as an oncogene by activating NF-κB/IL-6/STAT3 signaling [65]. Kshv-mir-K12-3 has been demonstrated to be a promoter of cell migration and invasion by targeting GRK2/CXCR2/AKT signaling [66], and kshv-miR-k12-1-5p has been shown to be a promoter of the proliferation, migration, and invasion of KS cells by suppressing cytokine signaling 6 (SOCS6) [67]. It has also been demonstrated that kshv-miR-K1-5p and kshv-miR-K4-5p directly target CASTOR1, inhibiting its expression and activating the mTORC1 pathway with the final result of promoting tumorigenesis [68].…”
Section: Kaposi's Sarcoma Herpesvirus/human Herpesvirus-8 (Kshv/hhv8)mentioning
confidence: 99%
“…And the epigenetic modi cation of the promoter region such as methylation has been proven to lead to down-regulation or loss of SOCS6 expression [19]. A more recent study has demonstrated that miR-k12-1-5p could lead to decreased expression of SOCS6 in Kaposi's sarcoma [20]. In glioblastoma, up-regulation of miR-494 could result in reduced expression of SOCS6 [21].…”
Section: Discussionmentioning
confidence: 99%
“…And the epigenetic modification of the promoter region such as methylation has been proven to lead to down-regulation or loss of SOCS6 expression [ 18 ]. A more recent study reported that miR-k12-1-5p could lead to decreased expression of SOCS6 in Kaposi’s sarcoma [ 19 ]. In glioblastoma, up-regulation of miR-494 could result in reduced expression of SOCS6 [ 20 ].…”
Section: Discussionmentioning
confidence: 99%